Anti-inflammatory activities of some Anthemis species used in the treatment of inflammation-related diseases, GC/MS and LC-MS/MS analysis with bioactivity-guided fractionation - Yldirim, Aybeniz; Gul, Abdulkadir; Basaran, Nihal; Sen, Ali; Bitis, Leyla; Tanyildizi, M. Saban (Elsevier, 2024)
Recent studies have focused on Anthemis sp. because of their rich chemical composition and application in the treatment of diseases associated with inflammation. The purpose of this study was to determine the active chemicals responsible for the anti-inflammatory properties of Anthemis cotula, A. tomentosa, A. austriaca, and A. tinctoria var. tinctoria. Therefore, the 5-Lipoxygenase (5-LOX) was used to assess the antiinflammatory properties of methanol extracts that were extracted from the aerial parts of the mentioned species, with an IC50 value of 23.88 mu g/mL, the methanol extract of A. tinctoria var. tinctoria demonstrated anti-inflammatory effects close to the standard (Indomethacin, IC50: 18.05 mu g/mL). Compared to the other extracts, the methanol extract of A. tinctoria var. tinctoria demonstrated significantly greater anti-inflammatory activity. A. tinctoria var. tinctoria and A. tomentosa methanol extracts, which were the most active in comparison to other extracts, were fractionated using the bioactivity-guided fractionation method. Their anti-inflammatory properties were evaluated to determine the compounds responsible for the activity. With an IC50 value of 3.44 mu g/mL, the ethyl acetate fraction of A. tinctoria var. tinctoria (ATiEA) was found to be the most active of all the fractions. After ATiEA was further fractionated using column chromatography, it was found that ATiEA-II, one of its sub-fractions, was more effective than other sub-fractions against the 5-LOX, with an IC50 value of 2.93 mu g/mL. Furthermore, the sub-fractions total phenol and flavonoid contents were examined to confirm their anti-inflammatory properties. The sub-fraction ATiEA-II exhibited higher total flavonoid content (743,86 mu g QE/g dry weight) and total phenol content (4659.36 mu g GA/g dry weight) than other sub-fractions, which was in line with its anti-inflammatory activity. GC/MS and LC-MS/MS were used to clarify the effective compounds of the sub-fraction ATiEA-II. Experiments on the anti-inflammatory properties of different Anthemis sp. have demonstrated the good anti-inflammatory potential of this species. Specifically, ATiEA-II, a sub-fraction of A. tinctoria var. tinctoria, may contain a novel anti-inflammatory drug molecule.
Keywords: Anthemis sp.; Anti-inflammatory; Sub-fractions; Bioactivity-guided fractionation